2021
DOI: 10.1289/ehp8949
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Transportation Noise and Risk of Incident Stroke: A Pooled Study of Nine Scandinavian Cohorts

Abstract: Background: Transportation noise is increasingly acknowledged as a cardiovascular risk factor, but the evidence base for an association with stroke is sparse. Objective: We aimed to investigate the association between transportation noise and stroke incidence in a large Scandinavian population. Methods: We harmonized and pooled data from nine Scandinavian cohorts (seven Swedish, two Danish), totaling 135,951 participants. We identified reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…However, the study had only 13 ischaemic and 21 haemorrhagic exposed cases. Notably, studies on transportation noise have also found positive associations with ischaemic stroke (and not haemorrhagic stroke),21 22 37 and with pathophysiological risk factors for ischaemic stroke including subclinical atherosclerosis and impaired endothelial function 5. This suggests the involvement of noise in causing vascular damage, and may provide a pathophysiological basis to explain the higher risk of ischaemic stroke in relation to occupational noise exposure.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the study had only 13 ischaemic and 21 haemorrhagic exposed cases. Notably, studies on transportation noise have also found positive associations with ischaemic stroke (and not haemorrhagic stroke),21 22 37 and with pathophysiological risk factors for ischaemic stroke including subclinical atherosclerosis and impaired endothelial function 5. This suggests the involvement of noise in causing vascular damage, and may provide a pathophysiological basis to explain the higher risk of ischaemic stroke in relation to occupational noise exposure.…”
Section: Discussionmentioning
confidence: 97%
“…Road traffic noise exposure was calculated based on each participant’s address history as the equivalent continuous A-weighted sound pressure level (L Aeq ) at the most exposed facade for day (07:00–19:00 hours), evening (19:00–22:00 hours) and night (22:00–07:00 hours), and expressed as L den 22. Road traffic noise for all cohorts was modelled using the Nordic Prediction method 35.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke is a complex multifactorial disease affected by multiple factors. According to previous studies, various factors including air pollution, transportation noise, smoking, substance abuse, and physical inactivity might be contributing factors to stroke [ 4 , 5 ]. In recent decades, emerging studies demonstrated the important role of air pollutants on stroke morbidity and mortality [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 , 8 In a recently published study in Environmental Health Perspectives , researchers assessed how exposure to transportation noise may affect stroke incidence. 9 …”
mentioning
confidence: 99%